2013
DOI: 10.1016/j.bios.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA stabilized silver nanoclusters for ratiometric and visual detection of Hg2+ and its immobilization in hydrogels

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…have been reported previously to template AgNCs with different emission properties [1,46]. For each sequence, the emission spectrum was measured at the excitation maximum in the visible region ( Figure 4).…”
Section: Changing the Template Dna Sequence It Is Well-established Tmentioning
confidence: 99%
“…have been reported previously to template AgNCs with different emission properties [1,46]. For each sequence, the emission spectrum was measured at the excitation maximum in the visible region ( Figure 4).…”
Section: Changing the Template Dna Sequence It Is Well-established Tmentioning
confidence: 99%
“…14). Recently, MacLean et al [102] reported a ratiometric detection of Hg 2+ using DNA stabilized Ag NCs with two emission peaks. The 620 nm red peak was quenched by Hg 2+ while the 520 nm green peak increased.…”
Section: Science China Materialsmentioning
confidence: 99%
“…In recent years, highly luminescent and stable nanoclusters have been extensively reported as fluorescence probes for a wide range of targets, including small ions [12,13], small molecules such as biothiols [14], hydrogen peroxide [15,16], glucose [17], amino acids [18], as well as nucleic acids [19], proteins [20] and other biological macromolecules [21,22]. Most of the detections were based on either the enhancement or the quenching of the fluorescence.…”
Section: Introductionmentioning
confidence: 99%